Diseño de una máquina para la construcción de ductos ovalados para un empresa del sector ventilación (2021)
The main objective of this project is to design a machine that builds oval ducts for a company in the ventilation sector, with the particularity that the process will be carried out starting directly from a galvanized steel strip and forming the spirally grafted oval duct without the need to make additional processes, just one process for the construction of these pipelines. Taking into account the current market, this process is not yet implemented, there are only studies in development, it is justified to carry out the project, representing an advance and innovation in the field of oval duct construction. The design process begins by collecting information on the pipeline manufacturing process to find out the current status of the process, followed by an explanation of the process involved in this project, specifying details and process parameters, to define the systems that the machine will have. After defining the systems, we proceed to make the detailed design of the systems, by means of the respective calculations and after this the manufacturing drawings of the systems. The conclusion of the project has the installation, operation and maintenance manuals for the machine, as well as an environmental analysis and project development costs.